Старые игрушки: стихи / Николай Година - Година Николай Иванович (Южно-Уральское книжное издательство, 1990)
Экземпляры: КХ (20111025) / Инвентарный номер: 966544 / Цена: 1.10 / Сис.шифр: Р2 / Авт.знак: Г 59 / ГРНТИ: 17 / ББК: 84(2)